Biofuels in Brazil: potentialities of Crambe abyssinica culture for biodiesel production - Queiroz, Isabela Reis (2021)
This article aimed to carry out a survey of the main characteristics of the oilseed Crambe abyssinica, covering from the ecology and morphology of the species to the conditions of cultivation and production of biodiesel. A qualitative study was performed through a literature review on the species and the production of biodiesel, analyzing bibliographic materials produced between the years 1970 and 2019 indexed in national and international databases. The results showed that due to the short cycle and the high production of triglycerides in the seeds, the species has a high potential for the production of biodiesel. In addition, the crop showed interesting characteristics for the producer, such as low production cost, tolerance to temperature variations and water stress, which can be used in crop rotation and as a ground cover plant. From the bibliographic review it was possible to describe the chromatographic profile of Crambe abyssinica oil and in addition verify the estimate of fossil fuel depletion for the next decades, associated with the increase in energy demand on the planet. The use of biodiesel is related to environmental factors insofar as it allows the reduction of toxic gas emissions and nutrients recycling and related to social and economic factors as it benefits rural producers, as demonstrated by the vast literature. In view of these considerations, the viability of Crambe abissynica cultivation to obtain raw material and the production of biodiesel was verified.